Prognostic and Predictive Significance of PD-L1 Expression in Non-Small Cell Lung Cancer Patients: A Single-Center Experience - Hacı ARAK; Aydın AYTEKIN; Ozlem CANOZ; Metin OZKAN (Türk Patoloji Dergisi, 2021)

(untitled)
Objective: To investigate the prognostic and predictive value of PD-L1 expression in operated non-small cell lung cancer (NSCLC) patients and to analyze its relationship with clinicopathological factors.